2008
DOI: 10.1103/physrevb.78.233311
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced current quantization in high-frequency electron pumps in a perpendicular magnetic field

Abstract: We present experimental results of high-frequency quantized charge pumping through a quantum dot formed by the electric field arising from applied voltages in a GaAs/AlGaAs system in the presence of a perpendicular magnetic field B. Clear changes are observed in the quantized current plateaus as a function of applied magnetic field. We report on the robustness in the length of the quantized plateaus and improvements in the quantization as a result of the applied B field.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 14 publications
3
35
0
Order By: Relevance
“…This option allows us to improve the flatness of the current plateaus by increasing the subband energy spacings. We found that the flatness of the first current plateau of ef at 100 MHz depends on the subband energy spacings and the result was comparable to that of the previous work without an external magnetic field [6]. Figure 1(a) shows the schematic diagram of the pump device.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…This option allows us to improve the flatness of the current plateaus by increasing the subband energy spacings. We found that the flatness of the first current plateau of ef at 100 MHz depends on the subband energy spacings and the result was comparable to that of the previous work without an external magnetic field [6]. Figure 1(a) shows the schematic diagram of the pump device.…”
Section: Introductionsupporting
confidence: 86%
“…Also parallelization of the pumps [5] is relatively easy with this technique. It has been found that high magnetic field helps to improve the accuracy of the pump current [6]. Despite of all the advantages that single-parameter pumping has, the subband energy spacings of the QD cannot be controlled separately with this method.…”
Section: Introductionmentioning
confidence: 98%
“…They showed that single-parameter pumping is robust in the sense that wide current plateaus appear in the parameter space but their measurement uncertainty was limited to about 10 À2 , and hence a detailed study of the behavior of the accuracy as a function of these parameters was not available. Wright et al (2008) made an important empirical observation that the accuracy of the single-parameter pump can be improved by an application of perpendicular-to-plane magnetic field [see also Wright et al (2009) and Fig. 25(b)].…”
Section: Experiments On Gallium Arsenide Quantum Dotsmentioning
confidence: 99%
“…The desired standard would generate the current I ¼ Nef by transferring N electrons per cycle at frequency f. Although notable achievements based on experiments with charge turnstile, 1-4 surface acoustic wave (SAW), [5][6][7][8][9] and single electron pumps [10][11][12][13][14] have reached, no fully satisfactory results in terms of both the accuracy and current magnitude have been realized yet. The exact mechanism of the current quantization is not fully understood, therefore, it is difficult to precisely design or simulate the devices.…”
Section: Introductionmentioning
confidence: 99%